Blackberry Production in México: Analysis of Profitability and Comparative Advantage (2023)
The production of blackberry is an issue that has become relevant over time due to the increase in the popularity of this berry, every day its use extends to more markets. The fact that its production requires specific geographical conditions and specific care, restricts the amount of supply in the international market, due to this it is noteworthy that in Mexico it presents the appropriate characteristics for planting and harvesting. Therefore, the objective of this work is to determine the profitability and comparative advantage of Mexican blackberry production for the year 2021, through the Policy Analysis Matrix (PAM). Among the main conclusions, it stands out that with a value of 0.3 and 0.53, it can be deduced that blackberry production is a competitive activity with an advantage for Mexican producers. JEL Codes: Q0, Q1, Q14, Q17 y Q18 Received: 27/11/2022.  Accepted: 11/03/2023.  Published: 04/04/2023.